Guide to the international registration of marks under the Madrid Agreement and the Madrid Protocol - World Intellectual Property Organization (Geneva, Switzerland World Intellectual Property Organization, 2016)
This Guide is primarily intended for applicants and holders of international registrations of marks, as well as officials of the competent administrations of the Member States of the Madrid Union. It leads them through the various steps of the international registration procedure and explains the essential provisions of the Madrid Agreement, the Madrid Protocol and the Common Regulations. Esta Guía está destinada principalmente a los solicitantes y titulares de registros internacionales de marcas, así como a los funcionarios de las administraciones competentes de los Estados miembros de la Unión de Madrid. Los guía a través de los diversos pasos del procedimiento de registro internacional y explica las disposiciones esenciales del Arreglo de Madrid, el Protocolo de Madrid y el Reglamento Común.
Keywords: MARCAS INTERNACIONALES -- PATENTES -- DERECHO INTERNACIONAL -- PROPIEDAD INTELECTUAL